Impacts of Typhoons on the Evolution of Surface Anticyclonic Eddies into Subsurface Anticyclonic Eddies in the Northwestern Subtropical Pacific Ocean - Shangzhan Cai; Jindian Xu; Weibo Wang; Chunsheng Jing; Kai Li; Junpeng Zhang; Fangfang Kuang (Remote Sensing)
In this study, we investigated the impacts of typhoons on the transformation of anticyclonic eddies (AEs) into subsurface anticyclonic eddies (SAEs) in the northwestern subtropical Pacific Ocean (NWSP) based on an ocean reanalysis product and multiple satellite observations. Results suggest that while the heavy precipitation and strong positive wind stress curl (WSC) induced by the passage of typhoons may be two main driving factors that transformed shallow mixed layer depth (MLD) AEs (i.e., those shallower than 50 m at the eddy core) into SAEs, the latter played a greater role in such transformation. In addition, shallow MLD AEs with a less depressed isopycnal structure near the eddy center before the passage of typhoons were more likely to be transformed into SAEs under the impacts of typhoons. The likely timing of such transformation may be within 9 days after the passage of typhoons. For deep MLD AEs (i.e., those deeper than 80 m at the eddy core), the impacts of typhoons may be much less prominent below the mixed layer. Based on a diagnostic analysis of the vertical potential vorticity (PV) flux at the surface, we examined the mechanism and dynamic processes involved in the transformation of deep MLD AEs into SAEs under the impacts of typhoons. Results show that while typhoons played a positive role in maintaining low PV within deep MLD AEs, which was favorable for further transformation into SAEs, the diabatic process associated with the net air–sea heat flux was the crucial favorable condition for the transformation of deep MLD AEs into SAEs.